Dual stimuli‐responsive microgels based on photolabile crosslinker: Temperature sensitivity and light‐induced degradation. Issue 12 (25th March 2014) - Bian, Shanshan; Zheng, Jin; Yang, Wuli
ABSTRACT The synthesis and characterization of a new photocleavable crosslinker is presented here. Dual stimuli‐responsive P(VCL‐co‐NHMA) microgels were prepared by precipitation polymerization of vinylcaprolactam (VCL) with N‐hydroxymethyl acrylamide (NHMA) and the new crosslinker. The microgels had distinct temperature sensitivity as observed in the case of PVCL‐based particles and their volume phase transition temperature (VPTT) shifted to higher temperature with increasing NHMA content. Photolytic degradation experiments were investigated by irradiation with UV light, which led to microgel disintegration caused by cleavage of the photolabile crosslinking points. The degradation behavior of the microgels was conducted with respect to degradation rates by means of the relative turbidity changes. Hence, the microgels could totally degrade into short linear polymers by UV light, thus representing a great potential as new light and temperature dual responsive nanoscale materials. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 1676–1685